Vzdělanostní struktura obyvatelstva v České republice se zřetelem na sociální skupinu osob se zdravotním postižením - Jeníčková, Jana (Lidé města, 2003)
The importance of the attained educational level in the Czech Republic is clearly seen in the registries of unemployment. It has been unequivocally demonstrated that the lower the education and qualification, the smaller the chance of finding a job. The unemployment rate is several times higher among those with elementary education than among those with high education, while the biggest discrepancy can be found between those with the elementary and university education. People with university education are the least afflicted by unemployment. In recent years, the unemployment rate surged in the Czech Republic, with low education of the Czech population probably being one of the causes. Among the handicapped, one can also see a direct connection between the educational level and opportunities for work. People with high education face less difficulties when looking for jobs and are less afflicted by the lay-offs. On average, people with „changed working ability" have lower education than the rest. The handicapped have mostly basic education or that without the school-leaving examination, while among the „healthy" part of the population, there is a dominance of secondary education. Competitive environment in the conditions of market economy reduces the number of jobs for the handicapped. ln general, it has been confirmed that the effort at raising education and qualification is one of the methods with which to increase employment, especially among the handicapped.